The impact of brand awareness and electronic word of mouth (e-wom), which are both mediated by brand image, on purchase intent for iPhone smartphone devices - Anggi Yunita Putri Anggi; Firman Firman (Marketing Management Studies, 2023)
This study aims to analyze "The Influence of Electronic Word of Mouth (E-WOM) and Brand Awareness on Purchase Intention for Iphone Smartphone Products Mediated by Brand Image (Studies in Communities Residing in Padang City)". The population in this study are people who live in the city of Padang who know about Iphone smartphone products. The number of samples in this study were 200 respondents. Data collection was carried out through online questionnaires or Google forms, data management using SmartPls 4.0 software. The results of this study indicate that (1) E-WOM has a positive and significant effect on Brand Image (2) Brand Awareness has a positive and significant effect on Brand Image (3) E-WOM has a positive and significant effect on Purchase Intention (4) Brand Awareness has a positive effect and significant to Purchase Intention (5) Brand Image has a positive and significant effect on Purchase Intention (6) E-WOM has a positive and significant effect on Purchase Intention for people who live in Padang city which is mediated by Brand Image (7) Brand Awareness has an effect positive and significant towards the Purchase Intention of the people who live in the city of Padang which is mediated by Brand Image.